Earn more tomorrow: Overconfident income expectations and consumer indebtedness - Antonia Grohmann; Lukas Menkhoff; Christoph Merkle; Renke Schmacker (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
This paper examines whether biased income expectations due to overconfidence lead to higher levels of debt-taking. In a lab experiment, participants can purchase goods by borrowing against their future income. We exogenously manipulate income expectations by letting income depend on relative performance in hard and easy quiz tasks. We successfully generate biased income expectations and show that participants with higher income expectations initially borrow more. Overconfident participants scale back their consumption after feedback. However, at the end of the experiment they remain with higher debt levels, which represent real financial losses. To assess the external validity, we find further evidence for the link between overconfidence and borrowing behavior in a representative survey (GSOEP-IS).
Keywords: D14; D84; G40; 330; Debt; Consumption; Borrowing; Overconfidence; Income Expectations